Nanoemulsions for drug delivery through different routes - Prakash U., Ravi Theaj; Thiagarajan, Padma (Research in Biotechnology, 2011)
Utilising nanoemulsions as vehicles for carrying active pharmaceutical ingredients is emerging as a promising approach for the latters’ targeted delivery. For drug molecules to be clinically effective, their administration by a route, which provides a proper channel for them to reach their target, is of prime importance. Further, they also need to be suitably protected in the biological milieu till they are delivered to the required site of action. Nanoemulsions with a mean droplet diameter of about 20-200 nm are extremely versatile in this regard. Due to their characteristic size and properties, which includes kinetic stability, they are very effective in enveloping and/or solubilising the drugs and successfully chaperoning them towards suitable targets. They also cause the drugs to be released in controlled and sustained modes, thereby reducing drug toxicity and dumping. Additionally, depending on the physiochemical properties of the drugs, nanoemulsions can be structurally engineered to maximize their solubilisation as per the required route of delivery, which is heavily dependent on the drug structure. Effective targeting can be achieved by incorporating suitable homing molecules on their surface, which in turn recognize and bind to specific receptors on the target molecules. This review focuses on the different routes by which drug loaded nanoemulsions can be administered, thus throwing light on the versatility of these vehicles for therapeutic and other related applications.